IDENTIFIKASI CALON MAHASISWA BARU DALAM PEMILIHAN PROGRAM STUDI SEBAGAI MODEL PENGEMBANGAN KERJASAMA DENGAN MKKS SE PROVINSI LAMPUNG - Helmy Fitriawan; Bambang Hermanto; Hery Dian Septana; Nandi Haerudin (Jurnal Komputasi, 2022)
There are still many prospective students from the University of Lampung from various high school graduates and their equivalent who do not know which study program at the University of Lampung is good and suitable for them, so that when they are accepted and start lectures, it is not uncommon for students to feel that they have chosen the wrong major which results in curiosity. changing study programs late or even unable to complete college. This study aims to build a decision support system that displays recommendations for Study Programs at the University of Lampung that are in accordance with the interests and academic abilities or intelligence of prospective students. This system is expected to assist prospective students in choosing a study program that suits them, so as to reduce the risk of changing study programs, as well as being late for graduation or even not being able to graduate. The system development method that will be carried out in this research is Extreme Programming (XP) in order to build a system quickly and according to user needs which has four main stages, namely planning, designing, coding, and testing before releasing the system. Meanwhile, to determine recommendations based on the interests and intelligence of prospective students, they will use Holland's theoretical basis for interest, and the Intelligence Structure Test (IST) theory for intelligence